Gemelos en la Casa de Maternidad de Madrid (1860-1899): Proporción y riesgo de muerte para los niños y las madres - Webinger, Katharina (Avisos de Viena, 2024)
Testimonies from the Maternity House provide a wealth of information about the experiences of mothers and infants in this public institution. Mothers could conceal their pregnancies and illegitimate births in this facility, where they were housed and cared for. One study focused on twins born in the Maternity House, analyzing records from 1860 to 1899. Data from three books, covering different periods, were transferred to Microsoft Excel for analysis. A total of 37 twin births were recorded, accounting for 2.12% of all registered births. Despite the lack of distinction between identical and fraternal twins in the available data, this study sheds light on the prevalence of twin births during the 19th century in Madrid's Maternity House.